New records of species of the family Rhopalidae (Heteroptera) in the province of La Pampa (Argentina) - Pall, José Luis María (2013)
At the global level are 18 genera that constitute Rhopalidae family in our country are only 5 genera, of which 3 are provided in this contribution to the province of La Pampa. The material comes from the entomological collection of the Museum of La Plata (Argentina) and campaigns conducted by the authors in the province of La Pampa.